2017
DOI: 10.1590/1980-5373-mr-2016-0934
|View full text |Cite
|
Sign up to set email alerts
|

Study of PtPd Bimetallic Nanoparticles for Fuel Cell Applications

Abstract: Bimetallic nanoparticles are of special interest for their potential applications for fuel cells, mainly for portable power applications. Among the bimetallic systems, Pt-Pd bimetallic nanoparticles have received great interest as they can be widely used as effective catalysts for various electrochemical reactions. In this work, Pt-Pd alloy bimetallic nanoparticles were synthesized through a chemical reduction method. The nanoparticles were characterized using aberration-corrected scanning/transmission electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…It can be clearly seen that the position of the (111) peak of PtPd (40.00°) is between that of pure Pt (39.89°) and pure Pd (40.15°) NPs. This is a clear indication of the formation of PtPd alloy . This is consistent to the fact that the Pt‐Pd system shows no (or negligible) miscibility gap for the whole range of concentrations, forming continuous and homogeneous solid solutions across the entire range of composition by alloying …”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…It can be clearly seen that the position of the (111) peak of PtPd (40.00°) is between that of pure Pt (39.89°) and pure Pd (40.15°) NPs. This is a clear indication of the formation of PtPd alloy . This is consistent to the fact that the Pt‐Pd system shows no (or negligible) miscibility gap for the whole range of concentrations, forming continuous and homogeneous solid solutions across the entire range of composition by alloying …”
Section: Resultssupporting
confidence: 83%
“…Indeed, Pd is able to absorb large amounts of hydrogen, but its hydrogen solubility decreases as the nanoparticle size decreases; on the other hand, Pt NPs exhibit effective hydrogen storage ability, although bulk Pt is a poor hydrogen absorber . These differences have prompted researchers to look for a possible use of these NPs in PtPd bimetallic structure to take advantage of the synergistic combination of the properties of both metals in the nanoscale form . In particular, in the field of catalysis, bimetallic NPs show superior catalytic properties than their monometallic counterparts .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in intensity brightness is an indicative of the presence of both Pd and Pt atoms at the surface. A study about the identification of the atoms in PdPt bimetallic alloy nanoparticles using HAADF-STEM images has been reported previously by our group [35]. This study showed a method semi-quantitative to analyze the atomic distribution of the elements which is dependent of their atomic number.…”
Section: Resultsmentioning
confidence: 88%
“…1(j) and (k) atomic-resolution HAADF and BF STEM images of the SnS 1.26 Se 0.76 ake viewed from the [001] axis. Since intensity of an atomic column in a HAADF STEM imaging mode is proportional to Z 1.7 (Z is atomic number), [32][33][34] the brightest spots (corresponding to the highest intensity line prole in Fig. S1(c) †) represent the Sn atomic columns (Z ¼ 50), while the medium-brightness and lowest-brightness spots (corresponding to the medium-high and lowest intensity line prole in Fig.…”
Section: Resultsmentioning
confidence: 99%